Motivational factors and job performance: the moderating roles of employee engagement / Hussain Ali Sulaiman Almawali - Almawali, Hussain Ali Sulaiman (2024)
Job performance pertains to the way individuals execute their assigned job duties and obligations. The optimisation of workplace efficiency and productivity is of utmost importance. Additionally, it demonstrates various significant aspects that influence the expansion, productivity, and advancement of the organisation. The primary objective of this research was to examine the impact of employee engagement on the relationship between motivational variables and job performance within the context of government employees in the Sultanate of Oman. The respondents for the study were employees from the Ministry of Labour, Oman. This study adopted a correlational research design, using quota sampling as the method for data collection. Data was collected via questionnaires consisting of four parts. Prior to the start of the real data gathering procedure, a pilot study was conducted to validate the instruments used. The data was analysed using the Statistical Package for the Social Sciences (SPSS) version 27. The gathered data was analysed using descriptive, correlational, multiple regression, and hierarchical regression analyses. The findings of this study revealed a significant association between motivational variables and job performance among the workforce of the Ministry of Labour. The study revealed that work environment emerged as the most influential element in predicting job performance, with training was identified as the second predictor. Using hierarchical regression analysis has shown that employee engagement acts as the moderator in the relationship between motivational factors and job performance among civil servants in Oman. The findings of the study also revealed that each aspect of employee engagement had a major role in influencing the relationship between motivational factors (training, compensation, work environment, and leadership) towards job performance. The researcher suggested several recommendations for improving work environment and fostering employee engagement. Organisations are advised to consider the physical environment, technological context and cultural environment as means to enhance employee work environment. At the same time, employers must assist their employees to manage stress effectively, foster employees’ well-being, and encourage self-management, ultimately leading to heightened levels of employee engagement. It is recommended that in future studies, scholars may explore and assess other forms of incentives given to employees within the public sector, examine additional elements beyond motivation that exert influence on job performance, and scrutinise a broader range of variables that serve as moderators.